ANALYSIS ON THE EFFECTIVENESS OF HOTEL TAX AND ITS CONTRIBUTION TO THE OWN-SOURCE REVENUE OF MALANG CITY (A case study at Local Revenue Service of Malang) - Yuwindasari, Putri (Jurnal Ilmiah Mahasiswa FEB, 2016)
The objectives of this study are to identify the effectiveness of hotel tax, the contribution of hotel tax to the own-source revenue of Malang, and the growth rate of  hotel  tax. Calculation  on  hotel  tax  potential  is  needed  to  identify  the effectiveness of hotel tax acceptance. The calculation is based on the number of hotels, hotel occupancy rate, number of rooms, room rate, average room rate, the number of days in a year, and the rate of hotel tax. Then, the effectiveness of hotel tax is calculated based on tax potential and tax realization. The method of this study is descriptive and quantitative, where the elaboration and the explanation of its dataare in the form of numbers. The author takes two hotels in Malang for each classification as the sample of her study. Based on the result of the study, it can be concluded that hotel tax acceptance during 2012-2-14 is not effective, that hotel tax contributes highly to the own-source revenue of Malang during 2012-214, and that the rate of hotel tax during 2012-2014 is increasing.Keywords: effectiveness of hotel tax, hotel tax contribution, hotel tax, local tax, own-source revenue